Mortality Rate and Causes of Death in Children Aged 1-59 Months in Northeastern Iran During 2011-2017 - Mehdi Safarpour; Amir Tiyuri; Parvin Mohamadzade; Maryam Dadjoo; Seyed Ahmad Hashemy; Masume Mohamadzade; Ehsan Shahrestanaki (Galenos Yayinevi, 2020)
Aim:The mortality rate indicator for children is one of the important indicators of population health and socioeconomic development of countries. In addition, to reduce the mortality in children, it is essential to determine causes of death. This study aims to determine the mortality causes in children aged 1-59 months in Northeastern Iran.Materials and Methods:This population-based cross-sectional study was conducted based on data from the child mortality surveillance system, from March 2011 to March 2017. The mortality rate was evaluated according to demographic variables (sex, place of residence and mother's education). Causes of death were coded according to the International Classification of Diseases. Chi-square and Mann-Whitney U tests were applied to investigate the relationships.Results:The mortality rate in children aged 1-59 months was 8.2 per 1,000 live births (CI 95%: 7.6-8.8) from 2011 to 2017. Totally 53.2% of mortalities occurred in boys (p=0.07). The frequency of death in the age group of 1-11 months was 1.7 times more than the age group of 12-59 months. The highest mortality rates occurred in rural areas and among children with illiterate mothers. During the study period, on average, the mortality rate decreased by 0.7 per 1,000 live births every year. The most common causes of death were unintentional accidents (33.8%) and congenital or chromosomal abnormalities (22.1%).Conclusion:Improving maternal education is among the key strategies for reducing child mortality. Therefore, it is necessary to raise the level of education and awareness regarding childhood mortality, especially in rural areas.